Research on the Influence of Unstable Incoming flow Parameters on DPF Regeneration Performance. Issue 2 (April 2021) - Li, Lu; Zhao, Zhichao; Wang, Yi; Meng, Zaiqiang; Liu, Qi
Abstract: Based on the simulation software, a regeneration simulation model of diesel particulate filter (DPF) was established, and the influence of unstable incoming flow parameters on its regeneration performance was studied. The results show that when the incoming flow is in an unstable state, the maximum temperature and maximum temperature gradient are lower than the steady state regeneration, with decreased regeneration efficiency. When the incoming flow temperature is in an unsteady state, 550°C is the critical temperature. When the incoming flow temperature is lower than 550°C, the maximum temperature and the maximum temperature gradient are higher than the steady state regeneration. When the incoming flow temperature is higher than 550°C, the maximum temperature and the maximum temperature gradient has little difference, with regeneration efficiency higher than that of steady state regeneration. When the oxygen concentration of incoming flow is in an unstable state, the maximum temperature is higher than the steady state regeneration. The maximum temperature gradient is higher than the steady state regeneration when the oxygen concentration is lower than 15%, and the difference is not significant, and vice versa, with the regeneration efficiency higher than the steady state regeneration.